New insights into the mechanisms of diastolic dysfunction in patients with type 2 diabetes. (June 2015) - Bayraktar, Al; Canpolat, Uğur; Demiri, Edis; Kunak, Ayşegül Ulgen; Ozer, Necla; Aksoyek, Serdar; Ovunc, Kenan; Ozkan, Adem; Yildiz, Okan Bülent; Atalar, Enver
Abstract Background. Little is known about the role of advanced glycation end products (AGEs) and their receptor (RAGE) in diabetic cardiovascular complications. Therefore, we aimed to evaluate the association of serum soluble RAGE (sRAGE) levels and left ventricular (LV) diastolic dysfunction in patients with type 2 diabetes. Methods. Our study consisted of 40 patients with type 2 diabetes and 40 age- and sex-matched healthy control group. Subjects with age ≥ 50 years old and any cardiovascular risk factors or conditions were excluded from the study. Serum sRAGE levels determined by enzyme-linked immunosorbent assay and LV diastolic dysfunction were evaluated according to current American Society of Echocardiography guidelines. Results. Baseline characteristics were similar between groups except body mass index, waist–hip ratio, and fasting glucose levels. Serum sRAGE level was significantly lower in diabetic group compared with control group (676 ± 128 vs. 1044 ± 344, p < 0.05). Diastolic dysfunction was observed in 50% of diabetic patients (40% grade I and 10% grade II). Correlation analysis showed that serum sRAGE was negatively correlated with duration of diabetes, septal E'/A', lateral E'/A', and average E/E'. In multivariate regression analysis, serum sRAGE level was strongly associated with diastolic dysfunction in patients with type 2 diabetes. Conclusion. Our study showed that serum sRAGE level was significantly lower in type 2 diabetic patients aged < 50 years old. Also, sRAGE has negative correlation with the duration of diabetes and it was significantly associated with the presence of diastolic dysfunction in type 2 diabetes.